PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP KUALITAS PELAYANAN PERPUSTAKAAN DI SMAN 1 SIJUNJUNG - Gusni Marlina; Marzalisman Marzalisman; Sinta Westika Putri (Jurnal Public Administration, Business and Rural Development Planning, 2021)
The objectives of the research carried out were 1. To determine the level of Interpersonal Communication at the Library of SMAN 1 Sijunjung 2. To determine the level of service quality for the library at SMAN 1 Sijunjung 3. To determine the effect of interpersonal communication on the quality of library services at SMAN 1 Sijunjung.The method used in this research is quantitative by using the survey method. Data collection techniques in this research are literature study, questionnaire questionnaire method and observation. The number of samples in this study were 60 students of class XII. The results of the study provide the following conclusions: 1 Level of Interpersonal Communication in the Library of SMAN 1 Sijunjung measured by the number of 17 items of questions to produce the accumulated average score s ebesar 363 with attainment percentage of TCR reached 71.27 so the interpersonal communication in the library SMAN 1 Sijunjung enough good . 2. The level of quality of service in the library SMAN 1 Sijunjung measured with 18 items of questions to produce the accumulated average score s ebesar 3702 with the achievement of the percentage of TCR reached 64.94%. So the quality of service in the library of SMAN 1 Sijunjung is not good. 3. Through regression test. Y = a + b XY = 11.089 + 0.748 (Interpersonal Communication) The constant value of the research results (a) is 11.089, this shows that the research results on Service Quality are purely without being influenced by independent variables of 10,587. The regression value (b) of 0.748 indicates a positive influence generated by Interpersonal Communication, meaning that if Interpersonal Communication (X) is increased by 1 point, it will have an influence on Service Quality of 0.748. From the results of the determination coefficient test through SPSS 21.00, the value of the determinant coefficient ( R - Square) of Interpersonal Communication (X) is 0.662 or 65.4%. Thus the variations in the increase and decrease in Service Quality (Y) can be explained by the Interpersonal Communication variable of 65.4%, while the remaining 34.6% Service Quality is influenced by other factors not included in the variables studied. Based on the hypothesis test (t test), the t value is 12,376, while the t table is 2.00. Thus t count> t table, so that (Ho) is rejected and (Ha) is accepted, meaning that there is an influence between Interpersonal Communication and Service Quality.